Dall’estetica alla teoria. Note sulla transestetica della letteratura (ENTHYMEMA, 2012)
Like Paul De Man pointed out, literary theory was born at the same time as literature itself, namely along with the birth of the early German Romanticism and its reflection about the nature of art. In this sense, literary theory is not opposed to the praxis of writing, while to its aesthetics, which we need therefore to overcome.